Symmetry‐Directed Self‐Assembly of a Tetrahedral Protein Cage Mediated by de Novo‐Designed Coiled Coils. (29th August 2017) - Badieyan, Somayesadat; Sciore, Aaron; Eschweiler, Joseph D.; Koldewey, Philipp; Cristie‐David, Ajitha S.; Ruotolo, Brandon T.; Bardwell, James C. A.; Su, Min; Marsh, E. Neil G.
Abstract: The organization of proteins into new hierarchical forms is an important challenge in synthetic biology. However, engineering new interactions between protein subunits is technically challenging and typically requires extensive redesign of protein–protein interfaces. We have developed a conceptually simple approach, based on symmetry principles, that uses short coiled‐coil domains to assemble proteins into higher‐order structures. Here, we demonstrate the assembly of a trimeric enzyme into a well‐defined tetrahedral cage. This was achieved by genetically fusing a trimeric coiled‐coil domain to its C terminus through a flexible polyglycine linker sequence. The linker length and coiled‐coil strength were the only parameters that needed to be optimized to obtain a high yield of correctly assembled protein cages. Abstract : Geometry lesson : A modular approach for assembling proteins into large‐scale geometric structures was developed in which coiled‐coil domains acted as "twist ties" to facilitate assembly. The geometry of the cage was specified primarily by the rotational symmetries of the coiled coil and building block protein and was largely independent of protein structural details.